The impact of executive team competency-sharing degree on firm innovation performance - Shao, Yueting; Qu, Liang; Liu, Pengzhen; Ding, Ling (Journal of Business Economics and Management, 2024)
In China’s high-quality development context, the key role of executive teams in corporate innovation is increasingly prominent. However, effectively utilizing the synergistic effect of competencies within these teams to boost innovation performance remains a crucial research issue. A sample of 2,350 companies in Shanghai and Shenzhen A-shares from 2010 to 2022 was used to examine the impact of the executive team’s capability-sharing degree on firm innovation performance. The study indicates that the degree of managerial competence sharing, entrepreneurial competence sharing, and technological competence sharing within the executive team positively impacts firm innovation performance. These findings remain robust in the face of variations in dependent variable measures, lagged independent variables, and the propensity score matching method. Environmental dynamism is identified as playing a positive moderating role in the relationship between the influence of managerial, entrepreneurial, and technological capability-sharing degrees and firm innovation performance. Further analysis of heterogeneity reveals that the impact of the executive team’s capability-sharing degree on firms’ innovation performance varies based on the nature of property rights, firm size, and industry competitiveness. This study, grounded in top-level ladder theory, offers a framework for enhancing team capabilities and overcoming growth obstacles through executive team competence sharing.